2012
DOI: 10.2139/ssrn.2054867
|View full text |Cite
|
Sign up to set email alerts
|

America’s Wetland? A National Survey of Willingness to Pay for Restoration of Louisiana’s Coastal Wetlands

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. A B S T R A C TA nationwide survey was conducted to estimate welfare associated with large-scale wetland restoration in coastal Louisiana. Binary-and multinomial-choice surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Kim, Petrolia, and Interis (2012) applied a new "quasi-double-referendum (QDR)" valuation technique to barrier island restoration in Mississippi. Finally, Petrolia, Interis, and Hwang (2014) conducted a nationwide survey to assess welfare benefits of wetland restoration in coastal Louisiana; respondents reported an average WTP a one-time tax of $909 per household.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Kim, Petrolia, and Interis (2012) applied a new "quasi-double-referendum (QDR)" valuation technique to barrier island restoration in Mississippi. Finally, Petrolia, Interis, and Hwang (2014) conducted a nationwide survey to assess welfare benefits of wetland restoration in coastal Louisiana; respondents reported an average WTP a one-time tax of $909 per household.…”
mentioning
confidence: 99%
“…Directly asking respondents about consequentiality issues could have provided valuable additional information. For example, Petrolia, Interis, and Hwang (2014) asked respondents 'how important did you think your vote would be . .…”
mentioning
confidence: 99%
“…In order for respondents to provide meaningful data, they need to believe that the survey is consequential and that their responses matter for policy purposes. At least two recent studies are designed to address consequentiality (Herriges et al 2010;Petrolia et al, 2014). Both appear to have fat tails, suggesting that a lack of Again, we see fat tails as a manifestation of hypothetical bias (the tendency of people to report a value other than their true value due to the hypothetical nature of a survey) and not an isolated contingent valuation issue.…”
Section: Discussionmentioning
confidence: 77%
“…As both Barbier (2013) and Börger et al (2014) point out, revealed preference methods such as hedonic and travel cost models are not applicable to many marine ecosystem services, such as those provided by the deep sea, due to a lack of any direct effect on market behavior from which to infer values. Thus, there may be a need for greater reliance on valuation estimates from bio-economic models (e.g., Barbier 2012; Barbier and Lee 2013;Fenichel and Abbott 2014;Tschirhart 2003a, 2003b;Sanchirico and Mumby 2009), or with the use of stated-preference methods, such as contingent valuation and choice experiments (e.g., Bagstad et al 2012;Bauer, Cyr, and Swallow 2004;Carlsson, Frykblom, and Liljenstolpe 2003;Holmes et al 2004;Moore, Holmes, and Bell 2011;Loomis et al 2000;Petrolia, Interis, and Hwang 2014), or contingent behavior, although the latter is geared less to valuation. As Börger et al (2014) point out, stated-preference methods require careful attention to survey designs to convey meaningful and understandable descriptions of ecosystem services to the general public.…”
Section: Emerging Research Direction: Ecosystem Services Valuationmentioning
confidence: 99%